ACCELEROMETER APPLICATION ON ANGKLUNG MUSICAL INSTRUMENT MOVEMENT RECOGNITION FOR BAMBOO BEAT VIDEO GAME - IQBAL (NIM : 13205037); Pembimbing : Dr. Ir. Hilwadi Hindersah, M.Sc., MUHAMMAD
Video games are games that involve user interaction to generate visual feedback. The use of sensors provide opportunities to design new kind of video games. Indonesia as a country with diverse cultural richness has a good potential to become a theme in video games. The author together with colleague from the Faculty of Arts and Design design a video game with angklung musical instrument as its theme. Angklung was designed to be integrated with the accelerometer so it can be used as an input device in the video game. The system consists of sensor module, microcontroller, and angklung musical instrument. Two accelerometers were being used to measure acceleration on the X, Y, and Z axis. Analog data from the accelerometer were processed by the microcontroller and sent to PC via serial port to gave data to the Visual Basic based software. The software will then control the game based on the data received. The system will distinguish three kind of movements which is centok, krulung, and tengkep. Characteristics of each movement was obtained from the test on several subjects including one who never played angklung before. Analysis of the characteristics done on time and frequency domain signal, but the algorithm is determined by analyzing the characteristics of the signal in time domain. The applied algorithm have 0,0371 s execution time which was considered low. The final test showed that the system can distinguish each angklung movement with 100% accuracy for centok, 96,66% for krulung, and 95% for tengkep. Angklung can be used as an input device for playing Bamboo Beat video game.